Development of an integrated aerobic granular sludge MBR and reverse osmosis process for municipal wastewater reclamation - Wang, Siyu (2021)
The reclamation of municipal wastewater to obtain high-grade product water is a growing need due to the pressing global water shortage. However, the existing municipal wastewater treatment plants (WWTPs) with the conventional activated sludge process as a core is not a sustainable engineering solution towards future water sustainability. To tackle such an emerging water-wastewater nexus, a ferrous-assisted aerobic granular sludge membrane bioreactor and reverse osmosis (AGSMBR-RO) process was developed for municipal wastewater reclamation. Results show that about 99.9%, 99.7% and nearly 100% of dissolved organic carbon (DOC), ammonium-N and total phosphorus (TP), respectively, could be removed in the ferrous-assisted AGSMBR-RO process, while the product water could meet the typical NEWater quality of Singapore with respect to the parameters analysed in this study. Moreover, it was found that an addition of 6 mg/L of ferrous could improve the stability of aerobic granular sludge (AGS) through the coagulation and flocculation of suspended flocs as well as phosphorus removal. These in turn led to reduced membrane fouling in both AGSMBR and RO units. Consequently, the proposed process is a promising alternative for municipal wastewater reclamation.